The Influence of Problem Based Learning on Critical Thinking Ability for Students in Optical Instrument Topic (Jurnal Pendidikan Fisika Indonesia, 2019)
The research aims to reveal the influence of the Problem Based Learning (PBL) model on students' critical thinking ability in optical instrument material. This research is a quasi-experimental research with Pre-test and Post-test Design. The subjects of this study were class X MAN 3 Malang. The experimental and control classes received PBL models and conventional learning models respectively. The instrument of this study was the Optical Instrument Critical Thinking Ability Test in the form of 14 essay questions with Cronbachâ€™s alpha reliability 0.78. The research data were analyzed using several tests including t-test, N-gain, and size effect tests. Based on the results of the analysis, it was shown that the implementation of the PBL model succeeded in increasing students' critical thinking ability higher than that of conventional learning. The experimental class was able to reach the high N-gain score category, while the control class was in the medium category. The research has a â€œlargeâ€ size effect category. This means that the PBL model implemented has a stronger influence than that of conventional learning in improving students' critical thinking ability. Thus, the PBL model can be recommended as an alternative learning model in improving students' critical thinking ability in physics learning on the topic of optical instruments.Penelitian bertujuan untuk mengungkap pengaruh model Problem Based Learning (PBL) terhadap kemampuan berpikir kritis siswa pada materi alat optik. Peneitian ini adalah penelitian kuasi eksperimen dengan Pre-test and Post-test Design. Subjek penelitian ini adalah siswa kelas X MAN 3 Malang. Kelas eksperimen dan kontrol, masing-masing menerima model PBL dan model pembelajaran konvensional. Instrumen penelitian ini adalah Tes Kemampuan Berpikir Kritis Alat Optik yang berupa 14 butir soal essay dengan reliabilitas alpha Cronbach 0,78. Data penelitian dianalisis dengan menggunakan beberapa uji antara lain uji-t, N-gain, dan size effect. Hasil analisis tersebut menunjukkan bahwa implementasi model PBL berhasil meningkatkan kemampuan berpikir kritis siswa lebih tinggi daripada pembelajaran konvensional. Kelas eksperimen mampu mencapai kategori N-gain score tinggi, sedangkan kelas kontrol pada kategori medium. Penelitian ini mampu mencapai size effect kategori â€œbesarâ€. Hal ini berarti model PBL yang diimplementasikan memiliki pengaruh kuat daripada implemnatasi pembelajaran konvensional dalam meningkatkan kemampuan berpikir kritis siswa. Dengan demikian, model PBL dapat direkomendasikan sebagai salah satu model pembelajaran alternatif dalam peningkatan kemampuan berpikir kritis siswa dalam pembelajaran fisika pada topik instrumen optik.